IJCM_30A: A mixed methods study to assess the contributory factors to anaemia among adolescent girls studying in tribal schools in a rural area of Maharashtra - Shinde Shwetangi; Sadawarte Deepika; Shet Neha; Singh Vijaykumar (Wolters Kluwer Medknow Publications, 2024)
Background: Anaemia is prevalent globally, notably in marginalized adolescent girls. NFHS-5 reports 59.1% anaemia in Indian adolescent girls. Tribal communities face unique health challenges due to their sociocultural dynamics. The national program for anaemia addresses this, but its implementation in contexts like tribal areas is unexplored. This study integrates quantitative and qualitative data for a thorough understanding of anaemia and its control in tribal settings. Objectives: 1. To estimate the prevalence of anaemia in tribal adolescent girls 2. To explore the awareness of anaemia in tribal adolescent girls 3. To understand the challenges in the implementation of an anaemia control program in a tribal setting Methodology: This 6-month mixed methods study assessed anaemia prevalence among adolescent girls in tribal schools. Using complete enumeration, a 200-sample size was determined, with obtained informed consent and assent. Adolescent girls were administered a questionnaire in their local language to collect information on their socio-demographic status and anaemia-related habits like diet and handwashing among others. Haemoglobin levels were measured using a digital haemoglobinometer. Focus Group Discussions with willing girls explored their understanding of anaemia, its causes and complications. Forced field analysis for ASHA and Anganwadi workers and certain Key Informant Interviews were conducted. Data was collected until saturation. Ethical approval with confidentiality was ensured. Results: The prevalence of anaemia was 70%, indicating a severe public health concern. Among these, 57.1% had mild, 34.3% had moderate, and 8.6% had severe anaemia. Anaemia in girls was statistically associated with specific food groups and habits. Low awareness of anaemia and operational issues in the control program were also identified. Conclusion: To enhance adolescent awareness of anaemia, efforts to improve their understanding of the condition and its impact are necessary. This research is vital for informing policymakers and health practitioners in refining interventions for this specific demographic in Maharashtra.